پیشین گوئیاں اور بعثت کی نشانیاں: پروفیسر عبدالقیوم کی تصنیف 'دائرہ معارف سیرتِ محمد رسول اللہ ﷺ' کی روشنی میں: PROPHECIES AND SIGNS OF THE PROPHETHOOD: IN THE LIGHT OF DAIRA-E-MA'ARIF SEERAT-E-MUHAMMAD RASOOL ALLAH ﷺ BY PROFESSOR ABDUL QAYYUM (Al-Aasar, 2025)
The prophethood of the Prophet Muhammad ﷺ was not an unexpected or spontaneous event; rather, it was a well-foretold reality, anticipated for centuries through divine scriptures, the teachings of former prophets, and the words of insightful individuals. Clear references to the Prophethood of Muhammad ﷺ were found in previous revealed books, which were not only known to the learned among the Jews and Christians, but they also conveyed these signs to their followers. These prophecies mentioned the person of the Prophet ﷺ, his attributes, the place of his emergence, the method of his call, and the impact of his mission. The prophets of Bani Israel particularly Prophet Musa (Moses) and Prophet ‘Isa (Jesus), peace be upon them had foretold the coming of a prophet who would be an "unlettered prophet" (an-nabiy al-ummi) and who would invite people to the oneness of God (Tawheed).Additionally, prior to his appointment as a prophet, both spiritual and physical signs manifested as preludes to this momentous event. These included the extinguishing of the fire temple of Persia, the dying out of the sacred flame in the oasis between Syria and Iraq, the Christian monk Bahira recognizing the Prophet ﷺ upon seeing him, and the dreams of certain elders of Quraysh indicating the arrival of a future messenger. These signs not only serve as evidence of the truthfulness of his Prophethood, but also point to the fact that the advent of the Prophet Muhammad ﷺ was part of a divine cosmic plan, prepared across different eras and nations. A critical analysis of these facts clearly shows that the Prophethood of Muhammad ﷺ was the final and most complete link in the great chain of Prophethood an arrival awaited not only by the People of the Book but by the spiritual conscience of the world.